Morphological Changes and Antihyperglycemic Effect of M. champaca Leaves Extract on Beta-cell in Alloxan Induced Diabetic Rats - Kritika Mehla, Devesh Chauhan, Satish Kumar, Anroop Nair, Sumeet Gupta* (Recent Research in Science and Technology, 2010)
Rapidly increasing diabetes mellitus is becoming a serious threat to mankind health in all parts of the world. The control of treatment depends upon the availability medicines without any side effects. Traditional anti-diabetic plants, which can counter the high cost and poor availability of the current medicines. So an attempt was made to study the beneficial effects of M. champaca leaves extracts on pancreas morphology of diabetic rat model. M. champaca leaf extracts (Ethanolic, Chloroform and Petroleum Ether) were administered at dose levels of 200 mg/kg body weight orally. A positive control and normal group received distilled water orally. Blood samples were collected from retro-orbital plexus of each rat and analyzed by GOD-POD test. After 21 days treatment among different extracts, the maximum reduction of serum glucose level showed significantly (p<0.001) treated with ethanolic extract 200mg/kg b.w. compared to diabetic control group. The serum lipids level was reversed towards normal treated with all extracts when compared to diabetic control group. Histological study of the pancreas also assesses the islets of diabetic control group were damaged, shrunken while islets of herbal extracts group reverse the effect of alloxan induction which clearly showed the regeneration of beta cells and their size. Ethanolic extract at dose of 200mg/kg b.w. brings about significant beneficial effects in various physiological/histological parameters altered diabetic manifestations.